2006
DOI: 10.1007/s00259-006-0193-4
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of myocardial blood flow response to cold pressor testing and pharmacologic vasodilation in healthy humans

Abstract: MBF response to sympathetic stimulation with cold (NO-mediated endothelium-dependent vasomotion), reflecting the functional state of the coronary endothelium, was independent of gender, age, and resting heart conditions. It was modulated by HDL cholesterol levels, even in healthy volunteers, and also related to pharmacologically stimulated vasodilator capacity at the coronary vascular resistance level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
57
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 26 publications
6
57
2
Order By: Relevance
“…We have also applied this approach in the risk assessment in smokers [13] and also applied the assessment of therapeutic interventions [4]. In the present study, CPT response and ΔCVR with 15 O-labeled water were impaired in smokers when compared to controls, in agreement with previous data [5,27,34]. In previous studies, a simple net retention model was applied for myocardial blood flow quantification using 82 Rb.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…We have also applied this approach in the risk assessment in smokers [13] and also applied the assessment of therapeutic interventions [4]. In the present study, CPT response and ΔCVR with 15 O-labeled water were impaired in smokers when compared to controls, in agreement with previous data [5,27,34]. In previous studies, a simple net retention model was applied for myocardial blood flow quantification using 82 Rb.…”
supporting
confidence: 77%
“…The ΔCVR, increase in absolute units, was defined as the difference between CVR during CPT and at rest [4][5]27]. 15 O-water and 82 Rb were assessed using intra-class correlation coefficients (ICC) [29] which is a best measure of reliability for continuous data and also evaluated graphically using a Bland and Altman plot which demonstrates not only the overall degree of agreement, but also whether the agreement is related to the underlying value of the item [30].…”
Section: Evaluation Of Cpt Response and Coronary Vascular Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…[65][66][67][68][69][70][71] Apart from methodologic differences in radiotracer characteristics, tracer kinetic models, and image analysis that may introduce some variations between different studies, the variability of the reported resting MBF values may be attributed in part to differences in myocardial workload and thus the myocardial oxygen demand of the left ventricle. 66,67,[72][73][74] Sex and genetic variations, including mitochondrial function, are also important determinants contributing to the variability in resting MBF values.…”
Section: Resting Mbfmentioning
confidence: 99%
“…66,68,82,83 Although the causes of this sex difference are not completely defined, hormonal effects on coronary circulatory function in women with CAD, and sex-dependent lipid profile changes, may be important contributors. 66,68,82,83 Finally, in individuals with advanced obesity, resting MBF may also be elevated as induced by a more enhanced activation of the sympathetic nervous system and the renin-angiotensin-aldosterone axis, resulting in higher resting heart rate and arterial blood pressure. 70,83,84 Physiologic Ranges for MBF and MFR with 13 N-Ammonia and 82 …”
Section: Resting Mbfmentioning
confidence: 99%